The Role of Metaphorical Thinking on Student’s Mathematical Reasoning Ability and Self Confidence - Pitria Susanti; Utari Sumarmo; Asep Kustiana ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
This research is a pretest-posttest experimental control group design having a goal to investigate the role of metaphorical thinking approach (MTA) toward students’ mathematical reasoning ability (MRA) and self-confidence (MSC). The research involves 64 eighth grade students of a Junior High School in Garut Indonesia, an MRA  test, and an MSC scale. The findings of this research were:  students getting treatment with MTA reached MRA at a moderate grade level, and students taught by  problem based learning (PBL) learning obtained MRA at a low grade level. However, there were no different grades on students’ MSC in both teaching approaches, and those grades were at a moderate level. Students in both teaching approaches encountered difficulties in solving MRA tasks such as on analogical reasoning about determine the value of the function, solving two linear variable equations, and writing down mathematical models involved in a calculation. Besides that, there was an association between MRA and MSC, students posed positive opinions toward implementation of MTA, and they performed active learning during MTA lessons.